2017
DOI: 10.1039/c7ra01354j
|View full text |Cite
|
Sign up to set email alerts
|

Simple and tunable surface coatings via polydopamine for modulating pharmacokinetics, cell uptake and biodistribution of polymeric nanoparticles

Abstract: A strategy that can modulate biological response such as pharmacokinetics, cell uptake and biodistribution of NPs simply by tunable coatings was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…The functionalization is based on a Schiff base type or Michael addition reaction between amine groups of BSA and catechol/quinine of polydopamine, which can be achieved through overnight incubation at room temperature. [ 45–47 ] After several washing steps with HyClone water, the particle's hydrodynamic diameter slightly increased to 513 ± 6 nm which gave a first indication that coating with BSA was successful. In addition, the zeta‐potential turned slightly negative after the coating procedure (‐19.4 ± 0.8 mV in HyClone water), providing further proof that the BSA coating was successful (Figure S2, violet bar, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The functionalization is based on a Schiff base type or Michael addition reaction between amine groups of BSA and catechol/quinine of polydopamine, which can be achieved through overnight incubation at room temperature. [ 45–47 ] After several washing steps with HyClone water, the particle's hydrodynamic diameter slightly increased to 513 ± 6 nm which gave a first indication that coating with BSA was successful. In addition, the zeta‐potential turned slightly negative after the coating procedure (‐19.4 ± 0.8 mV in HyClone water), providing further proof that the BSA coating was successful (Figure S2, violet bar, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…ABTS is used widely as a diffusional redox mediator for BOD or laccase bioelectrocatalytic activation. Moreover, polydopamine layers can conjugate lysine groups that are available on the protein surface; thus, BOD can be attached covalently to the electrode‐modified polymeric layer. An examination of the free lysine groups on the BOD (MvBOD, PDB, 2XLL) surface showed that Lys 21, 44, 181, 214, and 314 are in close vicinity to the T1 site and may be conjugated to the polymeric layer, which would improve the enzyme orientation with respect to the electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, as an excellent functional constituent material, PDA has an immense application scope, especially in the biomedicine. [ 10–14 ]…”
Section: Introductionmentioning
confidence: 99%